Nanoscale grinding: Unlocking the nutrient potential of oxidized phosphate rocks for sustainable fertilizer innovation - Houda A. Khedr; Mohamed O. Ebraheem; Hussah A. Alshwyeh; Najla F. Gumaah; Saedah Rwede AL-Mhyawi; Ahmed H. Ragab; Ahmed M. Zayed (PLoS ONE, 2025)
The current study delves into the transformative effects of intensive grinding to nanoscale upon oxidized phosphate rocks (PRs) of various grades, high (HMP), medium (MMP) and low (LMP) micro-sizes. Hence, the consequences of these transformative changes on phosphorous dissolution rate of these fractions using acetic acid, were carefully evaluated. The produced high (HNP) and medium (MNP) grades of nano-sized fractions revealed significant changes in their chemical composition, mineralogical, morphological and geometrical properties. Whereas the low grade, LNP, was moderately changed. HNP and MNP exhibited a remarkable increase in structural disorder (slight broadening of reflections) and Loss on Ignition (LOI) contents (10.62 and 13 wt.%, orderly), surpassing their counterparts (HMP: 6.04 and MMP: 10.92 wt.%). Despite the reduction in their P2O5 contents, HNP (31.23 wt.% and MNP (24.22 wt.%), astoundingly outperformed their micro-sized equivalents (HMP: 35.70 wt.%, MMP: 27.92 wt.%) in P dissolution. Therefore, HNP and MNP emerge as promising high-reactive P fertilizers for direct agricultural use and have a great potential as a source of P/Ca liquid fertilizer after nutrients balancing. So, eco-friendly grinding offers a potential approach to maximize PRs’ agronomic potential, but long-term environmental impacts should be evaluated.